49.5k views
2 votes
Please help with 3. And 4. above.... thanks for any help

Please help with 3. And 4. above.... thanks for any help-example-1
User Damccull
by
5.6k points

1 Answer

2 votes


f(x) = x^2 - 8x + 15 \ \ \ g(x) = x - 3\\f(x) - g(x) = x^2 - 8x + 15 - x + 3 = x^2 - 9x + 18\\(f(x))/(g(x)) = (x^2-8x+15)/(x-3) = x - 5, because \ x^2 - 8x + 15 = (x-3)(x-5)

User Mugunth
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.